We often need to convert inverse of cosec to either inverse of cos, sin, tan, sec , cot .In this post we will see how we can do it easily

## Inverse of cosec to inverse of sin

This is by property

$cosec^{-1} x = sin^{-1} \frac {1}{x}$

## Inverse of cosec to inverse of cos

**Case 1**

$cosec^{-1} x$ and x > 1

Now we can write as

$\theta=cosec^{-1} x$

$cosec \theta =x$

Now we know that here $\theta \in (0,\pi/2]$, so it is an acute angle

Now it can be written as

$cosec \theta =\frac {x}{1} = \frac {hyp}{perp}$

In Right angle triangle

Now then

$base = \sqrt {x^2 -1}$

Now

$cos \theta = \frac {base}{hyp} = \frac {\sqrt {x^2 -1}}{x}$

or $cosec^{-1}x = cos ^{-1} \frac {\sqrt {x^2 -1}}{x}$

**Case 1**

$cosec^{-1} x$ and x < -1

So value of the function will be in the range $[-\pi/2 , 0)$

Now we know from the property that

$cosec^{-1} (-x) = – cosec^{-1} (x)$

Therefore

$cosec^{-1} (x) = – cosec^{-1} |x| = – cos^{-1} \frac {\sqrt {x^2 -1}}{|x|} =cos^{-1} \frac {\sqrt {x^2 -1}}{x} – \pi $

This makes sense also as Range of the cosec and cos function differ. We can convert with out worrying about the sign in $[0, \pi/2]$ as it is common

Thus ,we have different formula depending on the values of x

## Inverse of cosec to inverse of tan

**Case 1**

$cosec^{-1} x$ and x > 1

from the above, we can write that

$tan \theta = \frac {perp}{base} = \frac {1}{\sqrt {x^2-1}}$

or

$cosec^{-1} x = tan^{-1} \frac {1}{\sqrt { x^2 -1}}$

**Case **2

$cosec^{-1} x$ and x < -1

Now we know from the property that

$cosec^{-1} (-x) = – cosec^{-1} (x)$

Therefore

$cosec^{-1} (x) = – cosec^{-1} |x| = – tan^{-1} \frac {1}{\sqrt {x^2-1}} $

Thus ,we have different formula depending on the values of x

## Inverse of cosec to inverse of sec

**Case 1**

$cosec^{-1} x$ and x > 1

from the above, we can write that

$sec \theta = \frac {hyp}{base} = \frac {x}{\sqrt {x^2-1}}$

or

$cosec^{-1} x = sec^{-1} \frac {x}{\sqrt { x^2 -1}}$

**Case **2

$cosec^{-1} x$ and x < -1

So value of the function will be in the range $[-\pi/2 , 0)$

Now we know from the property that

$cosec^{-1} (-x) = – cosec^{-1} (x)$

Therefore

$cosec^{-1} (x) = – cosec^{-1} |x| = – sec^{-1} \frac {|x|}{\sqrt {x^2 -1}} =sec^{-1} \frac {x}{\sqrt {x^2 -1}} – \pi $

This makes sense also as Range of the cosec and sec function differ. We can convert with out worrying about the sign in $[0, \pi/2]$ as it is common

Thus ,we have different formula depending on the values of x

## Inverse of cosec to inverse of cot

**Case 1**

$cosec^{-1} x$ and x > 1

from the above, we can write that

$cot \theta = \frac {base}{perp} = \sqrt {x^2-1}$

or

$cosec^{-1} x = cot^{-1} \sqrt { x^2 -1}$

**Case **2

$cosec^{-1} x$ and x < -1

So value of the function will be in the range $[-\pi/2 , 0)$

Now we know from the property that

$cosec^{-1} (-x) = – cosec^{-1} (x)$

Therefore

$cosec^{-1} (x) = – cosec^{-1} |x| = – cot^{-1} \sqrt {x^2 -1} $

This makes sense also as Range of the cosec and cot function differ. We can convert with out worrying about the sign in $[0, \pi/2]$ as it is common

Thus ,we have different formula depending on the values of x

I hope you like this article on how to convert cosec inverse x to sin, cos, tan, sec, cot inverse

**Related Articles**

how to convert cot inverse to sin, cos, tan, sec, cosec x inverse

how to convert sec inverse to sin, cos, tan, cosec x, cot inverse

how to convert sin inverse to cos, tan, sec, cosec x, cot inverse

how to convert cos inverse to sin, tan, cosec x, cot inverse

how to convert tan inverse to sin, cos, sec, cosec x, cot inverse